The Effect of the 5-HT4 Agonist, Prucalopride, on a Functional Magnetic Resonance Imaging Faces Task in the Healthy Human Brain - de Cates, Angharad N.; Martens, Marieke A. G.; Wright, Lucy C.; Gould van Praag, Cassandra D.; Capitão, Liliana P.; Gibson, Daisy; Cowen, Philip J.; Harmer, Catherine J.; Murphy, Susannah E. (Frontiers in Psychiatry, 2022)
Depression is a common and often recurrent illness with significant negative impact on a global scale. Current antidepressants are ineffective for up to one third of people with depression, many of whom experience persistent symptomatology. 5-HT4 receptor agonists show promise in both animal models of depression and cognitive deficit. We therefore studied the effect of the 5-HT4 partial agonist prucalopride (1mg daily for six days) on the neural processing of emotional faces in 43 healthy participants using a randomised placebo-controlled design. Participants receiving prucalopride were more accurate at identifying the gender of emotional faces. In whole brain analyses, prucalopride was also associated with reduced activation in a network of regions corresponding to the default mode network. However, there was no evidence that prucalopride treatment produced a positive bias in the neural processing of emotional faces. Our study provides further support for a pro-cognitive effect of 5-HT4 receptor agonism in humans. While our current behavioural and neural investigations do not suggest an antidepressant-like profile of prucalopride in humans, it will be important to study a wider dose range in future studies.